Butanol, 'a superior biofuel production from agricultural residues (renewable biomass): recent progress in technology - Qureshi, N.; Ezeji, T.C.
This article reviews bioconversion of plant materials such as wheat straw (WS), corn stover (CS), barley straw (BS), and switchgrass (SG)to butanol and process technology that converts these materials into this superior biofuel. Successful fermentation of low-value WS makes butanol fermentation economically attractive. Simultaneous hydrolysis, fermentation, and product recovery has been successfully performed in a single reactor using WS and C. beijerinckii P260. Research on the production of butanol from other agricultural residues including CS, BS, and SG has steadily progressed. Use of several product-recovery technologies such as liquid-liquid extraction, gas stripping, perstraction, and pervaporation has been successfully applied in laboratory-scale bioreactors. It is expected that these recovery technologies will play a major role in ommercialization of this fermentation. By employing in line/ in situ product-recovery systems during fermentation, butanol toxicity to the culture has been drastically reduced. In addition to the use of low-cost plant materials for the production of this biofuel, process integration is expected to play a major role in the economics of this product.
Keywords: BUTANOL; ACETONE-BUTANOL (AB); AGRICULTURAL RESIDUES; BIOREACTORS; PRODUCT RECOVERY; PROCESS INTEGRATION; FERMENTATION